Traces of Paleolithic expansion in the Nivkh gene pool based on data on autosomal SNP and Y chromosome polymorphism - V. N. Kharkov; N. A. Kolesnikov; L. V. Valikhova; A. A. Zarubin; A. L. Sukhomyasova; I. Yu. Khitrinskaya; V. A. Stepanov (Вавиловский журнал генетики и селекции)
The Nivkhs are a small ethnic group indigenous of the Russian Far East, living in the Khabarovsk Territory and on Sakhalin Island, descending from the ancient inhabitants of these territories. In the Nivkhs, a specific Sakhalin-Amur anthropological type is prevalent. They are quite isolated, due to long isolation from contacts with other peoples. The gene pool of the Nivkhs and other Far Eastern and Siberian populations was characterized using a genome-wide panel of autosomal single-nucleotide polymorphic markers and Y chromosome haplogroups. Bioinformatic processing of frequencies of autosomal SNPs, Y chromosome haplogroups and YSTR haplotypes showed that the Nivkh gene pool is very different from the other populations’. Analysis of the SNP frequencies using the PCA method divided the Far Eastern populations in full accordance with the territories of their residence into the northern group of the Chukchi and Koryaks and the southern group, including the Nivkhs and Udege. The remoteness of the Nivkhs coincides with their geographic localization, with the Nivkhs and Udege demonstrating the greatest kinship. The Nivkhs have a specific component of their gene pool, which is present with much less frequency in the Udege and Transbaikal Evenks. According to the IBD blocks, the genotypes of the Nivkhs show a very small percentage of coincidence with the Udege, Koryaks, Evenks and Chukchi, the value of which is the lowest compared to the IBD blocks among all other Siberian populations. The Nivkh-specific composition of haplogroups and YSTR haplotypes was shown. In the Nivkhs, the C2a1 haplogroup is divided into three sublines, which have a fairly ancient origin and are associated with the ancestors of modern northern Mongoloids. The Nivkh haplogroup O2a1b1a2a-F238 is found among residents of China and Myanmar. The Q1a1a1-M120 line is represented among the Nivkhs, Koryaks, Evenks and Yukaghirs. Phylogenetic analysis of individual Y chromosomal haplogroups demonstrated the closeness of the Nivkh gene pool with the ancient population of the Amur and Okhotsk regions, the Koryaks, the Tungus peoples and the population of Southeast Asia. The Nivkh gene pool confirms the relative smallness of their ancestral groups without mixing with other populations.